The Emergence of Member States’ Characteristics in European and National Consumer Law - Hajnal, Zsolt (The Policies of the European Union from a Central European Perspective, 2022)
European legislation often has a significant impact on private laws in the Member States, especially consumer legislation. In the absence of national, strong consumer protection traditions, consumer protection legislation in Central and Eastern European countries has been largely defined by European consumer law. In the chapter, I am looking for answers as to the specificities of these countries, their ability to enforce these in the EU’s main legislative trends, and how these countries have contributed to European Union consumer law.Keywords: EU consumer law, consumer contracts, ADR, warranty, guaranty, dual quality